The Effect of Teacher Professional Development and Work Motivation, Moderated by Principals’ Instructional Leadership, on Teacher Performance in Junior High Schools in Indragiri Hilir Regency - Khairunnisak Khairunnisak; Nurtanio Agus Purwanto (FKIP - Universitas Riau, 2026)
This study examines the effects of teacher professional development, work motivation, and principals’ instructional leadership on teacher performance in junior high schools in Gaung Anak Serka and Batang Tuaka. It analyzes the direct effects of professional development and motivation on performance, the direct effect of instructional leadership, and the moderating role of instructional leadership in both relationships. A quantitative ex post facto design was employed, involving 143 teachers selected as respondents. Data were collected using questionnaires and analyzed through Partial Least Squares–Structural Equation Modeling (SEM-PLS) focusing on hypothesis testing, moderation analysis, and model evaluation. The results show that teacher professional development significantly and positively affects performance (β = 0.485, p < 0.001), as does teacher motivation (β = 0.402, p < 0.001). Instructional leadership also has a strong positive effect on teacher performance (β = 0.558, p < 0.001). Furthermore, instructional leadership significantly moderates the relationship between professional development and performance (β = 0.437, p < 0.001) as well as between motivation and performance (β = 0.392, p < 0.001). These findings highlight the importance of strengthening principals’ instructional leadership while simultaneously promoting continuous professional development and enhancing teacher motivation to improve teacher performance.